VIEWS OF SAYED MUHAMMAD NAQUIB AL-ATTA’S ON DE-WESTERNIZATION OF KNOWLEDGE - Raz Mohammad Shirzad; Abdul Wahab Taib (CV. Radja Publika, 2024)
in an era marked by globalization and the dominance of Western paradigms in knowledge production, the call for de-Westernization has become increasingly imperative. This research delves into the profound insights of Sayed Muhammad Naquib al-Atta, a prominent Muslim philosopher, on the de-Westernization of knowledge. Al-Atta offers a nuanced critique of Western epistemological hegemony and presents a compelling framework for reorienting knowledge towards indigenous and Islamic perspectives. Central to Al-Atta’s discourse is the recognition of the interconnectedness between knowledge and culture. He elucidates how Western epistemologies, rooted in secularism and materialism, have not only marginalized non-Western traditions but also undermined the holistic understanding of reality. Al-Atta’s advocates for a reclamation of indigenous knowledge systems, emphasizing their integral role in shaping human consciousness and fostering spiritual enlightenment.